Exploring the Role of Skin Pigmentation in the Thermal Regulation of Polar Bears and Its Implications in the Development of Biomimetic Outdoor Apparel - Arny Leroy; David M. Anderson; Patrick Marshall; David Stark; Haskell W. Beckham (Textiles)
A popular belief for why polar bears have black skin is to increase solar heat gain from solar radiation that penetrates through a translucent fur layer made of unpigmented hollow hair. To examine the relative importance of skin color on solar heat gain, we measured thermal gradients, heat flux, and solar transmittance through a polar bear pelt under solar irradiation while thermally anchored to a temperature-controlled plate set to 33 °C. We found that for 60–70% of the dorsal region of the pelt where the fur layer is thickest, solar energy cannot reach the skin through the fur (solar transmittance ≤ 3.5 ± 0.2%) and therefore skin color does not meaningfully contribute to solar heat gain. In contrast, skin pigmentation was important in the remaining areas of the pelt that were covered with thinner fur. This information was used to select commercially available materials according to their solar optical properties to build biomimetic outdoor apparel with enhanced solar heat gain by a factor of 3 compared to standard outerwear constructions.